Comparative Evaluation of Different Impression Materials for Recording Tongue Morphology and Their Influence on Sex Determination: A Cross-sectional Forensic Odontology Study - Annu Gurjar; Monika Sharma; Radhika Saini (Asian Journal of Medicine and Health, 2026)
Background: Tongue morphology has potential as an adjunctive forensic marker, but the influence of impression material on the quality of tongue-morphology recording and subsequent sex determination requires comparative evaluation. Aim: To compare alginate, addition silicone, condensation silicone and polyether for recording tongue morphology and to assess their influence on sex-determination accuracy. Materials and Methods: This cross-sectional comparative observational study included 120 healthy adults (60 males and 60 females) aged 18–40 years. Each participant underwent tongue impression recording with the four materials. Two calibrated blinded observers assessed morphological reproduction, detail reproduction and dimensional stability. Participant comfort was rated on a 10-cm visual analogue scale. Sex-determination performance was evaluated using sensitivity, specificity and accuracy. Categorical variables were compared using the chi-square test, and continuous variables using one-way analysis of variance; p < 0.05 was considered statistically significant. Results: Addition silicone yielded the highest proportion of excellent detail reproduction (73.3%), followed by polyether (61.7%), condensation silicone (30.0%) and alginate (18.3%) (p < 0.001). Addition silicone showed the lowest dimensional change (0.24 ± 0.08%), whereas alginate had the highest comfort score (8.45 ± 0.82; p = 0.003). Sex-determination accuracy was highest with addition silicone (90.8%), followed by polyether (88.8%), condensation silicone (82.5%) and alginate (74.2%) (p < 0.001). Conclusion: Addition silicone provided the most favourable overall combination of detail reproduction, dimensional stability and sex-determination accuracy, while alginate offered greater participant comfort.